2012
DOI: 10.1136/archdischild-2012-302724.1594
|View full text |Cite
|
Sign up to set email alerts
|

1594 Laproscopic Cholecystectomy in the Pediatric Population: A Single Center Experience

Abstract: Background and Aims The aim of this study was to determine an appropriate postnatal management plan for prenatally diagnosed BCM including cystic biliary atresia (BA) and choledochal cyst (CC). Methods From 2002 to 2011, a total of 27 consecutive children with CC were treated at our institute. Eight of our 27 patients with CC were diagnosed prenatally and examined clinically. Of these 8 patients, 2 (Group A) underwent delayed primary definitive surgery after percutaneous transhepatic cholangiodrainage (PTCD), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
3
0
1
Order By: Relevance
“…6 Authors considered the 3-port approach to be mostly sufficient for cholecystectomy with a need for conversion to open cholecystectomy in 3 patients and postoperative complications due to failure of bile drainage in 3 patients (6). Accordingly, our findings are consistent with findings from published series of pediatric patients indicating efficacy and safety of laparoscopic cholecystectomy that results in short postoperative hospital stay and low complication rates (6)(7)(8)(9)14). Our findings also support the higher prevalence of idiopathic cholelithiasis as well as the association of cholelithiasis, particularly pigment stones containing bilirubin salts, with hemolytic disorders in the pediatric population (7,8,(14)(15)(16)(17) and the safety of laparoscopic cholecystectomy in the case of symptomatic cholelithiasis in pediatric patients with hemolytic disorders (5,18).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…6 Authors considered the 3-port approach to be mostly sufficient for cholecystectomy with a need for conversion to open cholecystectomy in 3 patients and postoperative complications due to failure of bile drainage in 3 patients (6). Accordingly, our findings are consistent with findings from published series of pediatric patients indicating efficacy and safety of laparoscopic cholecystectomy that results in short postoperative hospital stay and low complication rates (6)(7)(8)(9)14). Our findings also support the higher prevalence of idiopathic cholelithiasis as well as the association of cholelithiasis, particularly pigment stones containing bilirubin salts, with hemolytic disorders in the pediatric population (7,8,(14)(15)(16)(17) and the safety of laparoscopic cholecystectomy in the case of symptomatic cholelithiasis in pediatric patients with hemolytic disorders (5,18).…”
Section: Discussionsupporting
confidence: 91%
“…In another retrospective study of 202 pediatric patients with laparoscopic cholecystectomy, symptomatic cholelithiasis was reported to be the primary (46%) indication with concomitant splenectomy in 7.9% of patients. 9 Authors reported no common bile duct injuries, whereas spillage of bile in 5.9% and wound infection, retained stones, abdominal abscess, and biloma in 4.5% of patients (9). The median operative time and postoperative LOS were reported to be 117.5 minutes and 1 day, respectively (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a large retrospective series, Kelley-Quon et al [ 38 ] found a 0.36 % incidence of bile duct injury. Zeidan and colleagues [ 34 ] reported no bile duct injuries in 202 children undergoing LC. Thus, LC is safe and effective in children and there is no age-specifi c reason for children to be subjected to an open procedure.…”
Section: Laparoscopic Cholecystectomymentioning
confidence: 98%
“…En esta serie, un 84% son niñas; cifra superior a la reportada en otras series [4][5][6][12][13][14][15] . La coexistencia de coledocolitiasis (8,5% de los casos), es comparable con otras experiencias, tanto pediátricas como de adultos, por lo que no parece haber diferencia en la presentación de esta comorbilidad en este grupo de edad 13,16 . La morbimortalidad registrada, es similar a series de adultos, contrario a lo que uno pudiese pensar por ser sujetos anatómicamente más pequeños, hecho que pudiera significar un mayor riesgo de MPO 4,17 .…”
Section: Tabla 4 Enfermedades Concomitantes Verificadasunclassified